KEPADATAN POPULASI DAN TINGKAT SERANGAN HAMA SIPUT PADA BEBERAPA JENIS TANAMAN KEKUBISAN (Brassicaceae) DI DATARAN TINGGI GUNUNG MARAPI - Rusdi Rusli; Trimurti Habazar; Wanda Aningsih Gitri (Plant Protection Departement, Faculty of Agriculture, Universitas Andalas, 2021)
During the last three years, several snails as pests that attacked vegetables, especially cabbages (Brassicaceae) in the highland vegetable crop center of Mount Marapi, were found to cause damage. This study aimed to obtain the species, population, and attack rate of snails pests on the cabbage plants. The study was conducted using a survey method with purposive sampling conducted from July to September 2019 with the criteria of observing plants two weeks after planting and determining the sample diagonally. The results showed that cabbage plants in Mount Marapi, Agam Regency, were attacked by two snails, namely Bradybaena similaris and Parmarion sp. The population of B. similaris was higher than that of Parmarion sp. Mustard plants are most at risk of being attacked by snails, with the highest percentage and intensity of attack even though the damage category is classified as moderate. Mustard plants are also among the first time to be attacked by snails. Cultivation techniques affect the density and attack rate of pest snails at the research site. Key words: Slug attack level, species and population density, Bradybaena similaris, Parmarion sp.